Accelerating business transformation in the digital age - PAN, Gary (Institutional Knowledge at Singapore Management University, 2023)
Business Transformation involves making fundamental changes in how business is conducted in order to help cope with shifts in market environment. This chapter focuses on the role played by digital technology in business transformation and the mindset shifts required to embark on a digital transformation journey. More relevantly, this chapter also highlights how data analytics is driving digital transformation.